2019
DOI: 10.1088/1757-899x/571/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Cyperus Rotundus Extracted as Mouthwash on the Corrosion of Dental Amalgam

Abstract: Many extracted material were used as mouthwash to settle different kinds of oral fungi and bacteria. In this study an extractive of Cyperus rotundus plant E.C.R. which is very active as a mouthwash, was used in concentration range (10-25) ppm in artificial saliva at pH=6.4 and temperature range (288-318) K, to study it’s inhibitory effect on the corrosion of dental amalgam. Potentiostatic and cyclic polarization were used to follow this study. The presence of E.C.R. lead to shift the corrosion potential to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In fact, it is an expected result which essentially arises as a consequence of thyroid hormone action. In addition, T3 is responsible of inducing lipolysis in target cells and thus any decrease of T3 level would lead to the accumulation of the body fats [30], and thus, the energy intake and expenditure balance would be shifted and then weight is gradually increased [31,32]. Additionally, it has been suggested that OH causes weight gain by raising mucin deposition in the skin and other tissues, as well as water and salt retention [33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is an expected result which essentially arises as a consequence of thyroid hormone action. In addition, T3 is responsible of inducing lipolysis in target cells and thus any decrease of T3 level would lead to the accumulation of the body fats [30], and thus, the energy intake and expenditure balance would be shifted and then weight is gradually increased [31,32]. Additionally, it has been suggested that OH causes weight gain by raising mucin deposition in the skin and other tissues, as well as water and salt retention [33].…”
Section: Discussionmentioning
confidence: 99%
“…Langmuir model suggests a uniform surface with no interactions between adsorbed molecules [17]. The thermodynamic parameters of adsorption were calculated by using the following equations [15,18]: = -2.303RT log (55.5 ) (5) Log = (6) where T (K) is the absolute temperature, R is the gas constant (8.314 J.…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…The data in Table-2 show that i corr values for Gr.23 coated by Sr/Mg-HA before MAO treatment are lower (0.97 to 1.76 µA.cm -2 ) than those for uncoated Gr.23 (µA.cm -2 3.03 to 3.82). Protection efficiency (PE %) was calculated using the following equation [21,22]:…”
Section: Potentiostate Polarization Measurementsmentioning
confidence: 99%